Examining engineering students' perceptions of learner agency enactment in problem‐ and project‐based learning using Q methodology. Issue 1 (8th October 2021) - Du, Xiangyun; Lundberg, Adrian; Ayari, Mohamed A.; Naji, Khalid K.; Hawari, Alaa
Abstract: Background: Few studies have reported how students enact learner agency in a team setting or examined what elements of team settings students perceive as more supportive of their learning in problem‐ and project‐based learning (PBL) processes. Purpose: This study explores how engineering students perceive their enactment of learner agency, particularly which aspects of the PBL process they find most important. Method: Thirty‐nine students from two PBL civil engineering courses in Qatar participated in the study. Q methodology was chosen for both qualitative and quantitative data collection and analysis. A 40‐item Q set based on a theoretical model of learner agency was used. Results: Eight significantly different student viewpoints emerged from the Q methodological factor analysis, indicating a range of individual perceptions of learner agency. Intrapersonal dimensions were highlighted by three of the eight viewpoints, behavioral dimensions were underlined by seven viewpoints, and environmental dimensions were valued by all viewpoints. Conclusion: While the results reveal a wide range of individual experiences with learner agency across the three dimensions, students addressed self‐directed learning aspects both actively and passively, suggesting that many participants still value instructors' roles of providing direct instruction and authorized knowledge in PBL. The results highlight the need for more awareness of learner agency and more opportunities for students to enact learner agency by increasing PBL knowledge, skills, and efficacy. Q methodology can contribute to engineering education research by providing new theoretical and empirical insights into learners' subjective understanding of agency in a PBL setting as a complex system.